Cardiology emergencies - Brown, Jeremy, 1964-; Mazel, Jay (Oxford University Press, 2011)
Cardiology Emergencies covers the presentation, investigation, and management of acute cardiac problems that require speedy diagnosis and management. Created as a resource for residents and students, as well as an easy reference guide for physicians, this handbook is organized for quick access and learning. It is divided into three sections: the first provides acute presentations for quick diagnosis, the second addresses specific conditions, and the third offers clear descriptions of how to perform common practical cardiac procedures. Packed with concisely written summaries and bullet-point in.